Niveles de la hormona antimülleriana sobre la tasa de preñez en vacas brahman tratadas con un protocolo de inseminación artificial - Zambrano Mendoza, Johe Sebastián (2019)
This study consisted of evaluating the levels of the Antimüllerian Hormone on the pregnancy rate in Brahman cows treated with a fixed-time Artificial Insemination protocol (IATF). A descriptive study was implemented that measured the follicular size of luteal bodies, ovarian and pregnancy rate. Twenty-one Brahman cows were tested and sampled at the foot of> 3 deliveries, with body condition 3.5 (scale 1 to 5). The experimental units were grouped into three groups corresponding to three ranges of concentration range: AMH 0 to 220 ρg; AMH range 220 to 305 ρg and AMH range> 305 ρg. The data were analyzed with the statistical package SPSS for analysis of variance with P value <0.05. The study showed that AMH ranges influence the ovarian dynamics of Brahman cows treated with the (IATF) protocol. Animals with AMH ranges greater than 305 ρg / mL recorded an increase in dominant follicles (2 to 4 mm) (P≤0.001). Through logistic regression analysis, it was found that there is no relationship between the AMH ranges of empty and pregnant cows. A 52.4% chance of pregnancy was achieved when high plasma levels of AMH are found and an omnibus test with the model coefficients warned of a certain range of statistical efficiency in predicting the probability of pregnancy occurrence (Chi square 19.50; P <0.001) and a Wald significance and validity test below 0.01, which denotes a weak correlation between the variables studied. 43.0% pregnancy was confirmed in each range.